Income and Financial Trends for Kansas Farms - Langemeier, Michael R. (My University, 2010)
This publication uses data provided by farms enrolled in the Kansas Farm Management Association program to make income and financial ratio trends.
MF801_2010_12
Keywords: MF801; Economics; MF